2012
DOI: 10.1007/s10803-012-1686-6
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: CANTAB Performance and Brain Structure in Pediatric Patients with Asperger Syndrome

Abstract: By merging neuropsychological (CANTAB/cambridge neuropsychological test automated battery) and structural brain imaging data (voxel-based-morphometry) the present study sought to identify the neurocognitive correlates of executive functions in individuals with Asperger syndrome (AS) compared to healthy controls. Results disclosed subtle group differences regarding response speed on only one CANTAB subtest that is thought to tap fronto-executive network functions (SWM/spatial working memory). Across all partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…While in high-functioning adult individuals with autism spectrum disorder, behavioral performance was similar to a control group in a random-motor-generation task, group differences emerged regarding brain activity in the cerebellum (known to mediate motor learning and the coordination of voluntary movements, among others, e.g., [ 66 ]). Thus, the latter findings suggest that beyond prefrontal cortices, also extra-frontal regions may mediate autism-related behavior and performance characteristics (see, for example, recent connectivity studies [ 67 , 68 ] as well as respective structural brain imaging findings, e.g., [ 3 ]).…”
Section: Discussionmentioning
confidence: 95%
“…While in high-functioning adult individuals with autism spectrum disorder, behavioral performance was similar to a control group in a random-motor-generation task, group differences emerged regarding brain activity in the cerebellum (known to mediate motor learning and the coordination of voluntary movements, among others, e.g., [ 66 ]). Thus, the latter findings suggest that beyond prefrontal cortices, also extra-frontal regions may mediate autism-related behavior and performance characteristics (see, for example, recent connectivity studies [ 67 , 68 ] as well as respective structural brain imaging findings, e.g., [ 3 ]).…”
Section: Discussionmentioning
confidence: 95%
“…Deficits in EF abilities have been implicated in a number of neurodevelopmental disorders, including ADHD (Kofler et al, 2013), ASD (Kaufmann et al, 2013), Obsessive-Compulsive Disorder (OCD) (Hybel, Mortensen, Lambek, Thastum, & Thomsen, 2017), and DBDs (Wakschlag et al, 2018). Recent research in DBD populations has identified specific EF deficits, such as response inhibition (i.e., the ability to inhibit a prepotent response) and selective attention (i.e., the capacity to selectively attend to certain stimuli) (Friedman & Miyake, 2017).…”
Section: Neuropsychological Abilitiesmentioning
confidence: 99%
“…These tests have been successfully used in both healthy and clinical populations, including children with neurodevelopmental disorders and DBDs (Delmonte et al, 2012;Glenthøj et al, 2016;Lin & Gau, 2017;Luciana & Nelson, 2002;Robbins et al, 1994), and research has supported the construct validity of the CANTAB in measuring brain-behaviour relationships in adult psychiatric and neurological patient populations (Luciana & Nelson, 2002). Tests from the CANTAB battery were selected because they require minimal reading, are engaging for children as they are computerized and have a 'game-like' quality (participants use a press-pad or touchscreen), and once each task has been introduced and started it requires minimal interaction between tester and participant thereby reducing distraction and potential participant anxiety (Haring, Mottus, Koch, Trei, & Maron, 2015;Kaufmann et al, 2013). The following three subtests were used in the present study:…”
Section: Lca Indicatorsmentioning
confidence: 99%
“…Previous researches had provided inconclusive evidence about whether children with ASD are impaired in working memory. Investigations of school aged children and adolescents suggested working memory impairment in ASD [21,22]. Working memory deficit is associated with symptoms of children and adolescents with ASD such as communication and socialization impairments [23,24], restrictive and repetitive interests and behaviors [25].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies investigated the spatial working memory to confirm the dysfunction. However, whether children with ASD are impaired in the spatial working memory was not confirmed because of different measures used [21,30,31]. Furthermore, the visual perception requires executive functions such as planning and working memory, visual perception also affects the test results of spatial working memory.…”
Section: Introductionmentioning
confidence: 99%